Effectiveness and safety of acupuncture for cancer-related hiccups: a systematic review and meta-analysis - Guo, Zining; Liang, Ying; Liu, Wenhao; Huang, Bingjing; Zheng, Huiyan; Cui, Shaoyang; Xu, Nenggui (Frontiers in Neurology, 2024)
BackgroundThe use of acupuncture in cancer treatment is expanding. Nevertheless, the efficacy and safety of acupuncture in alleviating cancer-related hiccups remains uncertain and inconclusive.MethodsWe conducted a systematic search across eight databases: PubMed, China National Knowledge Infrastructure Database, WanFang, China Science and Technology Journal Database, SinoMed, Web of Science, Cochrane, and Embase, covering the period from their inception to July 2023. Literature was screened based on predefined PICOS inclusion and exclusion criteria, and the risk of bias was assessed using the Cochrane Risk of Bias tool. Data synthesis was performed using Review Manager 5.3 software and R studio 4.4. Additionally, we conducted a frequency analysis of acupoint usage.ResultsA total of nine randomized controlled trials (RCTs) involving 580 patients were included in the analysis. The risk of bias assessment indicated a high risk of bias in all nine RCTs, primarily due to blinding of participants and personnel and random sequence generation (selection bias). The meta-analysis revealed that acupuncture significantly reduced the symptoms of cancer-related hiccups compared to pharmacological treatment (relative risk (RR) = 1.83, 95% confidence interval (CI) [1.53, 2.20], p < 0.001, I2 = 27%). In terms of onset time, acupuncture demonstrated a shorter duration of onset compared to pharmacological treatment (mean difference (MD) = −8.71, 95% CI [−23.32 5.89], p < 0.01, I2 = 100%). Furthermore, acupuncture exhibited a significant improvement in sleep, eating, and appetite scores compared to pharmacological treatment (MD = 0.68, 95% CI [0.07, 1.29], p = 0.03; MD = 0.68, 95% CI [0.07, 1.30], p = 0.03; MD = 0.66, 95% CI [0.08, 1.25, p = 0.03]). The frequency of acupoint usage was analyzed, with ST36 and PC6 being the most frequently used acupoints. Regarding adverse events, acupuncture exhibited favorable safety profiles compared to other control groups.ConclusionThe meta-analysis results suggest that acupuncture has a positive effect on the efficacy rate for cancer-related hiccups, as well as improvements in quality of life and time to effect response. However, due to the high risk of bias and quality limitations of the included studies, no conclusive evidence currently supports the efficacy of acupuncture. High-quality, evidence-based research is still needed to confirm the effectiveness of acupuncture in treating cancer-related hiccups.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, CRD42023451403.